IMPRENSA DE COMUNIDADES IMIGRANTES DE SÃO PAULO E IDENTIDADE: estudo dos jornais ibéricos Mundo Lusíada e Alborada - Escudero, Camila (2007)
Among the press directed toward colonies of immigrants in circulation at São Paulo city, currently (2005/2006), there are Mundo Lusíada (Portuguese) and Alborada (Spanish). To identify if those two periodicals bring in their content, predominantly, subjects that favor the cultural change and assimilation of the foreigner in the receiving territory or the preservation of its cultural identity is the main objective of this work, besides of selecting the publishing characteristics and inquiring if the relation with the community in question is not only a marketing strategy. The study was based on bibliographical research, mapping the main publications, directed toward immigrants, which circulate in São Paulo and, over all, the content analysis of 12 editions of the Mundo Lusíada and 11 of Alborada. Among the observed results, it is distinguished that the content of both provides elements that propitiate a direct contact with those groups roots. This demonstrates elements that spread the collective memory of the Portuguese and Hispanic immigrants who had come to Brazil more than a century ago - independently if this identity is real. Although Mundo Lusíada is a vehicle directed toward the Portuguese-Brazilian community, it is segmented, because, among others factors, it uses the commercial structure of a small company. Alborada can be considered communitarian in the sense of serving the attended by the Sociedade Hispano Brasileira - SHB (that it sponsors it) - but this character is changing. About journalistic aspects verified on the two periodicals, those are similar to the small press, in a mixture of amateurish and source of status. However, both have important paper in strengthen the bows of friendship, cultural and union of the involved, as well as in the celebration of their origins.(AU)